2018
DOI: 10.3390/app8040519
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis and Noise-Reducing Design of an Outside Rear View Mirror

Abstract: The outside rear view mirror (OSRVM) is installed on the exterior of vehicles to secure the side and rear views of the vehicle, but its extruded design causes unwanted aerodynamic noise and vibration during driving. In this study, additional line holes (inner dents) are made on the inner and outer edges of the mirror housing without a reduction in size in order to enhance the aerodynamic flow and noise around the mirror. Based on computational fluid dynamics (CFD) analysis, this study compares the aerodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…These studies show that maximum noise in air friction is produced by body protuberances, i.e., mirrors, elerons, spoilers. The noise values produced by them are relatively smaller (50-90 dB) than the values which we are tracking [58].…”
Section: Results From Stand Analysismentioning
confidence: 62%
“…These studies show that maximum noise in air friction is produced by body protuberances, i.e., mirrors, elerons, spoilers. The noise values produced by them are relatively smaller (50-90 dB) than the values which we are tracking [58].…”
Section: Results From Stand Analysismentioning
confidence: 62%
“…The numerical results of this work have showed in Fig 39 and Fig 40. The results showed that with the use of indentation mirrors, the pressure oscillations and vortices in the back of the mirror reduced and therefore noise level reduced (Fig 41). Moreover, Yong-Ju Chu et al [77] in a recent published work examined the effect of a side mirror on the level of sound generated by an automobile. In this work, two new designs include side mirror with internal and external duct investigated (Fig 42).…”
Section: Aeroacoustics In Automobile Industrymentioning
confidence: 99%
“…Consequently, minor slippage occurs due to the difference between the frictional and propulsive forces of the contact surface, resulting in energy loss. The slip is defined as a dimensionless quantity, which is a percentage of the forward speed, as in Equation (2). Hence, the potential energy ratio delivered to the stone can be calculated using the slip ratio:…”
Section: Tire Geometry and Numerical Modelmentioning
confidence: 99%
“…Therefore, the severe design considerations of underbody shield against the impact of external bodies or random stone chipping needs to be made. As the driving performance of newly developed automobiles is rapidly improving and the maximum driving speed is gradually increasing, aerodynamic noise, vibration and harshness (NVH) become significant in passenger vehicles [2]. Moreover, most public roads, other than toll expressways, are difficult to maintain, and roads damaged by aging due to seasonal changes are rapidly destroyed.…”
Section: Introductionmentioning
confidence: 99%